AZT exerts its antitumoral effect by telomeric and non-telomeric effects in a mammary adenocarcinoma model - Armando, Romina Gabriela (2016)
Limitless replicative potential is one of the hallmarks of cancer that is mainly due to the activity of telomerase. This holoenzyme maintains telomere length, adding TTAGGG repetitions at the end of chromosomes in each cell division. In addition to this function, there are extratelomeric roles of telomerase that are involved in cancer promoting events. It has been demonstrated that TERT, the catalytic component of telomerase, acts as a transcriptional modulator in many signaling pathways. Taking into account this evidence and our experience on the study of azidothymidine (AZT) as an inhibitor of telomerase activity, the present study analyzes the effect of AZT on some telomeric and extratelomeric activities. To carry out the present study, we evaluated the transcription of genes that are modulated by the Wnt/β-catenin pathway, such as c-Myc and cyclin-D1 (Cyc-D1) and cell processes related with their expression, such as, proliferation, modifications of the actin cytoskeleton, cell migration and cell cycle in a mammary carcinoma cell line (F3II). Results obtained after treatment with AZT (600 µM) for 15 passages confirmed the inhibitory effect on telomerase. Regarding extratelomeric activities, our results showed a decrease of 64, 38 and 25% in the transcription of c-Myc, Cyc-D1 and TERT, respectively (p<0.05) after AZT treatment. Furthermore, we found an effect on cell migration, reaching an inhibition of 48% (p<0.05) and a significant passage-dependent increase on cell doubling time during treatment. Finally, we evaluated the effect on cell cycle, obtaining a decline in G0/G1 in AZT-treated cells. These results allow us to postulate that AZT is not only an inhibitor of telomerase activity, but also a potential modulator of extratelomeric processes involved in cancer promotion.